Third party cord blood transplant boosts autologous hematopoiesis in a case of persistent bone marrow aplasia after double transplant failure for β-thalassemia major - Giuseppe Visani; Paola Picardi; Barbara Guiduccu; Claudio Giardini; Moira Lucesole; Sara Barulli; Teresa Ricciardi; Federica Loscocco; Alessandro Isidori (Mediterranean Journal of Hematology and Infectious Diseases)
A 9-year-old female received a double allogeneic stem cell transplant (SCT) from an ABO-incompatible HLA-matched sibling for β-thalassemia major, without achieving a complete donor chimerism. Subsequently, the patient received autologous SCT and five donor lymphocyte infusion, without increasing donor chimerism. After the double transplant failure, we performed an unrelated transplant from a full-matched umbilical cord blood (UCBT). Due to the severe immunosuppression of the patient, we did not administer any conditioning regimen nor GVHD prophylaxis. On day +40 after UCBT, trilinear engraftment was documented. Surprisingly, the hematopoietic reconstitution was related to the re-expansion of the autologous (β-thalassemic) hematopoietic stem cell, as documented by chimerism studies on both peripheral blood and bone marrow. At present, 30 months after UCBT, there is stable hematopoietic autologous reconstitution. This is the first description of the restoration of autologous hematopoiesis obtained with cord blood infusion in a thalassemia-major patient after a double transplant failure.